Early maladaptive schemas in relation to facets of psychopathy and institutional violence in offenders with personality disorders - Chakhssi, Farid (Legal and criminological psychology, 2014)
Purpose Current knowledge suggests that the psychopathy construct is multifaceted in nature, and reflects different underlying pathological mechanisms, including neurobiological dysfunction and maladaptive cognitions. Although many contemporary studies focus on neurobiological aspects of psychopathy, few have addressed the maladaptive cognitions. Method In this study, we examined facets of Hare's psychopathy construct in terms of their associations with maladaptive cognitions, as defined by Young's cognitive theory of Early Maladaptive Schemas (EMS). Personality disordered offenders (N = 124) were assessed with the PCL-R and the Young Schema Questionnaire. Results The PCL-R Lifestyle and Antisocial Facets were significantly related to EMS Mistrust/Abuse and Insufficient Self-Control, consistent with our hypotheses, and were significantly, but negatively, related to EMS Subjugation. Also as hypothesized, EMS showed no associations with the PCL-R Affective and Interpersonal facets. Contrary to our expectation, EMS did not predict institutional violence. Conclusion Our findings suggest that schemas relating to mistrust, inadequate self-control/low frustration tolerance, and autonomy/dominance, play a role in the impulsive lifestyle and antisocial behaviour features of psychopathy. Treatments that focus on ameliorating these schemas may lead to better outcomes in psychopathic offenders.